An Alternative Assessment Approach Towards Learning Natural Sciences Communication - Chung, Hung Hui (UNIMAS Publisher, 2023)
In STF2083 Scientific Communication, traditional written examinations were reduced to 30% using various types of alternative assessments which include (i) forums writing and online quizzes, (ii) mock research proposal presentation, (iii) mock research proposal writing and (iv) poster presentation . Instructions as well as rubrics were given to students prior to commencing of the assessments. Referring to the theme ‘Justify the basic principles in executing research’ as stated in CLO2 and ‘Display writing skills and presenting scientific reports’ in CLO3, the assessment of this course highlighted four (4) main sections; (a) identification of major/important need to conduct research (Problem statement identification), (b) the means to understand/solve the arising problems (hypothesis deduction), (c) the measurable target within the scope of this intended research (objectives determination) and (d) steps involved in achieving the outlined objectives (experimental design). In this course, all four types of assessments (i.e. mock research proposal writing, mock research proposal presentation, poster presentation and online forums) are individual-based assessment. The reason for such course design is to ensure individual performance is aligned with the intended assessment (authentic assessment).